The Ability of Mesenchymal Stem Cells for Periodontal Tissue Regeneration: A Comprehensive Review of Literature - MohammadMostafa Aghamohseni; Shirin Zahra Farhad (Isfahan University of Medical Sciences, 2022)
Stem cells and tissue engineering have shown great potential in the treatment of periodontal diseases since their introduction. Mesenchymalstem cells are undifferentiated cells that can differentiate into different tissues. The aim of this study was to evaluate the effectiveness of different types of these cells in the treatment of periodontal defects.Description:Mesenchymal stem cells exist around different tissues and can be obtained and used from different intraoral or extraoral sources for periodontal tissue regeneration procedures. Among extracellular stem cells, bone marrow stem cells followed by adipose tissue stem cells have shown promising results regarding the ability of these cells to regenerate the periodontium. Among intraoral sources, periodontal ligament mesenchymal stem cells and then dental pulp cells have shown more results and ability compared to other cell types to regenerate periodontal tissue. Periodontal ligament stem cells have also been able to generate sharpey fibers in periodontal regeneration procedures in various studies.Conclusion:Mesenchymal stem cells have shown promising results for use in periodontal tissue regeneration processes. However, due to the limited clinical and preclinical studies performed so far, more studies are needed for assessing the clinical use of these generative of cells